Use of a urease inhibitor to mitigate ammonia emissions from urine patches. Issue 1 (2nd January 2021) - Rodriguez, Maria Jimena; Saggar, Surinder; Berben, Peter; Palmada, Thilak; Lopez-Villalobos, Nicolas; Pal, Pranoy
ABSTRACT: Urine deposition by grazing livestock is the single largest source of ammonia (NH3 ) volatilisation losses in New Zealand. Urease inhibitors (UI) have been used to mitigate NH3 losses from fertiliser urea and animal urine. In previous trials, the UI effect in reducing NH3 emissions from urine has been measured by applying urine mixed with the UI to the pasture soil thus increasing the chances of better interaction of the UI in inhibiting the urease enzyme. However, these trials do not represent a realistic grazing scenario where only urine is deposited onto the soil. This current research aimed to identify the best time to spray nBTPT (a UI containing 0.025% N -( n -butyl) thiophosphoric triamide) onto pasture soil to reduce NH3 losses from urine patches. The treatments were: a control (without urine and nBTPT), urine alone at 530 kg N ha –1 and urine plus nBTPT. The UI was applied to the chambers and soil plots 5 and 3 days prior to urine deposition, on the same day and 1, 3 and 5 after urine deposition in autumn. Ammonia losses were measured using the dynamic chamber method. The application of the inhibitor prior to urine deposition reduced NH3 losses with reductions of 27.6% and 17.5% achieved for UAgr-5 and UAgr-3, respectively. However, reductions in NH3 emission were 0.6–2.9% for inhibitor applied post urine deposition. There was also a reduction in both soil NH4 + –N concentration and soil pH in comparison with urine alone or with the treatments where nBTPT was applied after urine deposition. GRAPHICAL ABSTRACT: UF0001